The Impact of Education Existence Based on Pondok Pesantren in Drenges Village - Diah Puji Nali Brata; Maria Lusiana Nurohmasari (EDUTEC : Journal of Education And Technology, 2020)
development is the most important aspect of community life in a country. The development of education is hampered by the way schools prioritize aspects of knowledge. Thus, boarding school-based education is needed as an educational institution that teaches knowledge, character, and skills. The existence of Islamic boarding school-based education as the oldest educational institution in Indonesia is still maintained by some people. For this reason, the importance of discussing the topic of the existence of Islamic boarding school-based education is to provide knowledge about how Islamic boarding schools show their existence in the development of community education. The purpose of this study was to determine the supporting factors of Islamic boarding schools in developing community education and the impact of the existence of Islamic boarding school-based education on the development of education for the community in Drenges Village. The method used in this research is the qualitative method. Research data obtained by interview, observation, and documentation. The results showed that the factors that support Islamic boarding schools in developing community education are the quality of teachers, the curriculum used, and learning activities. Meanwhile, the impact of the existence of boarding school-based education for the Drenges community is the increase in aspects of knowledge, skills, and the character of independence. The importance of the research results is to provide a view to modern society that Islamic boarding school-based institutions can encourage the development of community education.